Synthesis of Dialkyl-1,1-diacetyl-8a-hydroxy-8-oxo-1,2,8,8atetrahydrocyclopenta[ a]indene-2,3-dicarboxylates from the Reaction of Dialkyl-2-(1-acetyl-2-oxopropyl)-3- (tributylphosphoranylidene)succinates with Indene-1,2,3-trione - RAMAZANI, ALI; AHMADI, EBRAHIM; YOUSEFTABAR MIRI, LEILA; JAFARI, ALI; HEIDARI, AZAM (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates produced in the reaction between tributylphosphine and dialkyl acetylenedicarboxylates by acetylacetone leads to sterically congested phosphorus ylides. Reaction between the sterically congested phosphorus ylides with ninhydrin leads to stereoselective synthesis of dialkyl 1,1-diacetyl-8a-hydroxy-8-oxo-1,2,8,8a-tetrahydrocyclopenta[a]indene-2,3-carboxylates in the presence of Magnesium sulfate powder under microwave irradiation (1 KW, 3 min) in solvent-free conditions.